Modeling the impact of external factors on the euro area's HICP and real economy: a focus on pass-through and the trade balance - Luigi Landolfo (European Central Bank (ECB), 2007)
This paper aims to analyze the impact of external factors, such as the nominal effective exchange rate, foreign demand and the terms of trade, on the euro area real economy. In particular, the paper estimates the quantitative impact that changes in these factors have on net trade, real GDP and the Harmonized Consumer Price Index (HICP). To this end, we estimate a Dynamic Simultaneous Equation Model (DSEM) accounting for the presence of key exogenous variables. The tool utilized here to measure the impact of various shocks on the real economy is the impulse response function. The study is also conducted at sub-components level. First, we estimate the model replacing net trade with its sub-components, namely, the volume of exports and the volume of imports. Then, we re-estimate the model by dividing the terms of trade index into import and export prices. Overall, we estimate three models. Two of these models show consistent results. We found that the nominal effective exchange rate and foreign demand are the main determinants of the trade balance. Nevertheless, while foreign demand strongly affects real GDP, the nominal effective exchange rate affects it only slightly. Among the external factors, foreign demand has the strongest impact on real GDP. Regarding the impact of the nominal effective exchange rate on import prices and HICP, we found that the exchange rate pass-through for the euro area is not very high. This result is broadly in line with the findings presented in Hahn (2003).
Keywords: C32; E52; 330; ECB; Net trade; Real economy; Eurozone; Konjunkturzusammenhang; Verbraucherpreisindex; Terms of Trade; Kaufkraftparität; Exchange Rate Pass-Through; Handelsbilanz; EU-Staaten